Parameterization of the APSIM-Oats model for simulating the growth of black oat cultivated for forage purposes under cut-and-carry management - Débora Pantojo de Souza; Cristiam Bosi; Fernando Campos Mendonça; José Ricardo Macedo Pezzopane (Acta Scientiarum: Agronomy)
Studies on modeling the growth of annual crops are typically conducted for economically significant crops like soybeans, corn, and wheat. Conversely, there has been limited exploration of annual forage crops, despite their substantial importance, as they can help address forage supply shortages during periods of low production for perennial tropical forages. This study aimed to parameterize the APSIM-Oats model for simulating the growth of black oats (Avena strigosa Schreb cv. IAPAR 61 Ibiporã) cultivated for forage purposes and managed under a cut-and-carry system. Two experiments were conducted in 2018 and 2019 in Piracicaba, São Paulo State, Brazil, encompassing both irrigated and non-irrigated plots. Various productive, biometric, and soil moisture variables were monitored throughout the crop cycles. Parameters were manually calibrated through a trial-and-error process until the estimates closely matched the observed data. Model evaluation involved comparing observed and simulated data using statistical indices. The most favorable results were obtained for live biomass, leaf mass, and stem mass (with modeling efficiency exceeding 0.55 in the rainfed system and surpassing 0.34 for the irrigated system). Estimates of soil water content exhibited better accuracy for shallower soil layers (0 to 0.30 m). The calibration of the APSIM-Oats model for black oats yielded satisfactory estimates for live biomass under rainfed conditions. The simulations in this study represent an initial step in modeling the growth of black oats.